Phenotypic spectrum in families with mesial temporal lobe epilepsy probands - Emilija Cvetkovska; Igor Kuzmanovski; Marija Babunovska; Bojan Boshkovski; Tatjana Cepreganova Cangovska; Gordana Kiteva Trencevska (Elsevier BV, 2018)
The traditional perception of mesial temporal lobe epilepsy (MTLE) as a predominantly acquired disorder is challenged due to emerging evidence of familial aggregation. In this study, we ascertained the extent of familial occurrence of epilepsy in MTLE patients, as well as phenotypic heterogeneity in affected relatives.